Translation of Adverbs of Manner from English to Indonesian: Content Analysis of Charlotte’s Web Novel by E. B. White - Resty Widya Kurniasari (GoAcademica Research & Publishing, 2020)
The purpose of this research is to obtain an overall view of the translation of adverbs of manner from English to Bahasa Indonesia. This study used a qualitative approach using a content analysis method. The data used in this study are all sentences which are positive, negative, and interrogative sentences, including translation strategies and translation shifts (of the meaning). The data source in this study is Charlotte’s Web novel by E.B. White in English as the source text and the translation in Bahasa Indonesia (Laba-laba dan Jaring Kesayangannya) as the target text translated by Dina Begum.